2017
DOI: 10.1186/s12943-017-0718-4
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNAs and miRNA dysregulation in cancer-associated fibroblasts

Abstract: PurposeThe present review aimed to assess the role of exosomal miRNAs in cancer-associated fibroblasts (CAFs), normal fibroblasts (NFs), and cancer cells. The roles of exosomal miRNAs and miRNA dysregulation in CAF formation and activation were summarized.MethodsAll relevant publications were retrieved from the PubMed database, with key words such as CAFs, CAF, stromal fibroblasts, cancer-associated fibroblasts, miRNA, exosomal, exosome, and similar terms.ResultsRecent studies have revealed that CAFs, NFs, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
179
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(183 citation statements)
references
References 116 publications
3
179
0
1
Order By: Relevance
“…However, as we learn more about miRNAs, it is clear that generalization about a particular miRNA being oncogenic or a tumor suppressor depends on cellular context. miRNAs are involved in the post-transcriptional regulation of genes involved in EMT, stemness, cell signaling pathways, and regulation of the tumor microenvironment, including the conversion of normal fibroblasts into cancer-associated fibroblasts (CAFs) by transfer of exosomal miRNAs from tumor cells (reviewed in (Yang, et al 2017a)). An issue in the field is the lack of congruence of miRNAs identified for a particular cancer type, e.g., thyroid cancer, even within a subtype, in different studies.…”
Section: The Chronology Of Mirna Discovery Was Recently Reviewed (Drumentioning
confidence: 99%
See 1 more Smart Citation
“…However, as we learn more about miRNAs, it is clear that generalization about a particular miRNA being oncogenic or a tumor suppressor depends on cellular context. miRNAs are involved in the post-transcriptional regulation of genes involved in EMT, stemness, cell signaling pathways, and regulation of the tumor microenvironment, including the conversion of normal fibroblasts into cancer-associated fibroblasts (CAFs) by transfer of exosomal miRNAs from tumor cells (reviewed in (Yang, et al 2017a)). An issue in the field is the lack of congruence of miRNAs identified for a particular cancer type, e.g., thyroid cancer, even within a subtype, in different studies.…”
Section: The Chronology Of Mirna Discovery Was Recently Reviewed (Drumentioning
confidence: 99%
“…CAFs stimulate cancer progression by secreting chemokines, cytokines, and growth factors that create the extracellular matrix (ECM) and CAFs secrete EVs containing a different spectrum of miRNAs compared to normal fibroblasts (Bayraktar et al 2017). Among the miRNAs secreted by CAFs that regulate cancer cells are miR-21, miR-143, and miR-378 in BCa (Donnarumma, et al 2017); miR-210, miR-409-3p/5p (Yang et al 2017a), andmiR-409 (Josson, et al 2014) in PCa cells; and miR-21 in ovarian cancer (Au Yeung, et al 2016). Tumor-associated macrophages (TAMs) are also donors of miRNAs in cancer (reviewed in (Bayraktar et al 2017)).…”
Section: Mirnas In Circulationmentioning
confidence: 99%
“…A wide range of biological processes including cell proliferation, apoptosis, invasion, and migration have been identified to be regulated by miRNAs [7, 8]. Thus, the deregulated expression of miRNAs has been associated with various diseases including cancers [9-12].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the potential role of miRNAs secreted by exosomes in CAFs in the ability of cancer cells to migrate and invade cannot be ruled out. Exosomal miR-NAs can be taken up by bystander cells and functionally delivered as a mechanism of cell-to-cell communication (Bach et al 2017;Bayraktar et al 2017;Yang et al 2017). However, it has been demonstrated that the secreted miRNA expression pattern does not always match that of endogenous miRNAs (Valadi et al 2007;Pigati et al 2010).…”
Section: Discussionmentioning
confidence: 99%